2017
DOI: 10.3389/fpsyg.2017.00361
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Reactivity to Arousing Stimuli with Social and Non-social Relevance in Alexithymia

Abstract: Emotional difficulties in alexithymia and their social consequences have been linked to alterations in autonomic nervous system. However, most of previous studies did not take into account the distinction between the affective and the cognitive dimensions of the alexithymia, leading to inconsistent results.Aim: In this study, we compared the effects of both dimensions of alexithymia on the autonomic arousal to emotional and social visual stimulations.Methods: Skin conductance responses (SCRs) to items of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 72 publications
(146 reference statements)
3
8
0
Order By: Relevance
“…The data on explicit emotion recognition are in line with those of the previous studies on alexithymia and recognition of emotional faces or scenes (Kano et al 2003;Meriau et al 2006;Pollatos et al 2008, Heinzel et al 2010Lee et al 2011;Pollatos and Grahaman 2011;Scarpazza et al 2014Scarpazza et al , 2015Martinez-Velazques et al 2017;see;Grynberg et al 2012 for a review), where HA participants were consistently found to have normal explicit emotion recognition capabilities. Alexithymia is associated with poor explicit emotion recognition only when stimuli are presented under temporal constraints (Ihme et al 2014;Parker et al 2005) or when the emotion is expressed at a low intensity (Starita et al in revision;Swart et al 2009).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The data on explicit emotion recognition are in line with those of the previous studies on alexithymia and recognition of emotional faces or scenes (Kano et al 2003;Meriau et al 2006;Pollatos et al 2008, Heinzel et al 2010Lee et al 2011;Pollatos and Grahaman 2011;Scarpazza et al 2014Scarpazza et al , 2015Martinez-Velazques et al 2017;see;Grynberg et al 2012 for a review), where HA participants were consistently found to have normal explicit emotion recognition capabilities. Alexithymia is associated with poor explicit emotion recognition only when stimuli are presented under temporal constraints (Ihme et al 2014;Parker et al 2005) or when the emotion is expressed at a low intensity (Starita et al in revision;Swart et al 2009).…”
Section: Discussionsupporting
confidence: 89%
“…A previous study suggested that a person's empathic ability predicts the degree to which that person produces RFRs in response to others' emotional expressions (Hussey and Safford 2009). Both our group (Scarpazza et al 2014) and other groups (for instance: Moriguchi et al 2007;Martinez-Velazques et al 2017;Sonnby-Borgstrom 2009) have previously demonstrated reduced empathic abilities in HA participants relative to LA participants using the IRI. The new aspect of the present study is the correlation between somato-motor embodiment of emotions (measured by RFR magnitude) and empathic ability (measured by the IRI perspective taking score).…”
Section: Discussionsupporting
confidence: 48%
“…As indicated, we also observed that participants of LE group exhibited a high score in alexithymia, a difficulty to identify, analyze, and express emotional experiences (Sifneos, 1973;van der Velde et al, 2013) widely related to deficits in social skills (Goerlich et al, 2012;Martínez-Velázquez et al, 2017). In fact, the observed negative association between empathy trait and alexithymia levels fits well with observations reported in previous studies (Fossati et al, 2009;Moral and Ramos-Basurto, 2015).…”
Section: Alexithymia Levelsupporting
confidence: 91%
“…Considering that previous research has linked alexithymia trait with empathy trait (Moral and Ramos-Basurto, 2015;Martínez-Velázquez et al, 2017), the alexithymia trait was assessed by using Spanish version (Moral, 2008) of the Toronto Alexithymia Scale . This version has shown good reliability (α = 0.82) and stability indices in the Latin American population.…”
Section: Toronto Alexithymia Scalementioning
confidence: 99%
See 1 more Smart Citation